Interactive Effects of Residue and Tillage Methods on Growth, Yield and Yield Components of Melon - Ehsan Neamatollahi; Morteza Akbari; Reza Tavakol Afshari; Mohammad Alizadeh Noughani (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2021)
Field experiments were conducted to investigate the effects of residue and tillage on growth and yield of melon. Tillage treatments included conventional tillage (using a moldboard plough and two passes with a disk harrow), minimum tillage (one pass with a disk harrow), and no tillage (NT). Residue treatments included the application of 0%, 30% and 60% residue. Yield and yield components were obtained for all treatments. Tillage significantly affected yield and its components (P ≤ 0.05). The maximum FWPP (2.678 kg), NFPP (6.799), D (18.49 cm), L (45.93 cm), S (12.51%) and RUE (2.470) and yield (16.17 t/ha) were recorded in the conventional tillage treatment. Also, maximum FWPP (2.192 kg), NFPP (5.353), D (16.66 cm), L (39.52 cm) and yield (12.83 t/ha) were observed in the 30% residue treatment. In terms of the interaction effects, maximum FWPP (2.850 kg), NFPP (6.790), D (20.71 cm), L (53.53 cm) and yield (17.09 t/ha) were obtained in the conventional tillage + 30% residue treatment. Therefore, the use of a moldboard plough followed by two passes with a disk harrow, in concert with 30% residue treatment, were maximizing the yield Almost all growth indicators had the optimum values in the conservation tillage treatments.